Metode Perancangan Sambungan Balok Bangunan Baru terhadap Kolom Eksisting Rumah Sakit Umum Daerah Al – Ihsan - Choly Nuradil (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
Along with the rapid development of construction, especially in terms of efficiency and safety, the use of alternative materials such as steel and precast concrete has become increasingly popular. One important aspect of building construction is the connection between new structures and existing ones. This study aims to compare the methods of connecting new beams to existing columns at the Al-Ihsan General Hospital, using two types of connectors, namely steel connectors and anchor connectors, in the context of efficient and safe connections. The buildings studied are Buildings D, F, and G, which fall into the risk category IV, with a seismic importance factor of 1.50. The method used in this analysis is seismic analysis using the ETABS program for structural modeling and internal force calculations. The analysis evaluates the strength and performance of connections using anchors as the link between new beams and existing columns compared to connections using steel connectors. The analysis results show that the use of anchors in beam-column connections not only provides time efficiency but also exhibits equal or even better strength than the use of steel connectors, making it a more efficient alternative in designing connections for buildings linked to existing structures.